The Relationship between Academics and Administrative Staff in Selected Nigerian Universities. - Ojutiku, Doyinsola Eniola Mrs (Obafemi Awolowo University, 2014)
This thesis examined the causes of such conflicts that are noticeable between the academic and the administrative staff groups in the Universities of Ibadan, Ife and Lagos. It attempts to determine whether conflict is caused by an organizational structure which places decision-making powers in the hands of academics with little direct participation by other staff groups.